Sistema experimental para realização de ensaios não-destrutivos magnéticos e sua aplicação na avaliação da degradação microestrutural do aço A516 grau 60 - Praxedes, Thomas de Oliveira (2012)
The magnetic properties of ferromagnetic materials are greatly influenced by the microstructure and stresses. Thus, the evaluation of the magnetic behavior of structural materials can be used for characterization of its internal state. This paper develops a experimental measurement system for non-destructive testing based on the evaluation of the magnetic characteristics of the material and its correlation with the state of stress and its microstructure. The system was used to evaluate the microstructural degradation caused by plastic deformation of A516 grade 60 steel, through cold rolling process. A sensor was designed and built to perform both the magnetization and the monitoring of magnetic behavior of the material tested. Sensor operating parameters such as frequency, current and thickness of the air gap between the sensor and the surface of the material were studied by simulation with finite element method. Among the tests performed by the system is the testing of magnetic anisotropy, which gets the value of the flux density at various angles relative to the rolling direction. The hysteresis test obtains the hysteresis loop of the material from which it is possible to extract the magnetic parameters coercive field and hysteresis losses, which have a direct correlation with the degree of plastic deformation. The magnetocrystalline energy testing provides a direct assessment of anisotropy between the axes parallel and perpendicular to the rolling direction. The testing of analysis of minor hysteresis loops uses triangular excitation, which enables a direct assessment of the differential magnetic permeability, which is very sensitive to the internal state of the material and provides a visualization of how the process of magnetization is influenced by plastic deformation and residual stresses . The tests showed results consistent with the final state caused by the process of cold rolling and similar research on the literature, providing an satisfactory characterization of the state of the studied material.